Place of Angioplasty for Coronary Artery Anomalies With Interarterial Course - Aubry, Pierre; Halna du Fretay, Xavier; Boudvillain, Olivier; Degrell, Philippe, The ANOCOR Working Group (Frontiers in Cardiovascular Medicine, 2021)
Few patients with an anomalous aortic origin of a coronary artery (AAOCA) require a correction of this congenital anomaly. Current recommendations offer surgical repair as a first line therapy to prevent a sudden cardiac death as a main objective. However, these guidelines are focused on children and not based on randomized controlled studies. Furthermore, decision-making should be different in an adult population less exposed to the risk of sudden cardiac death. Current practices showed reluctance to offer a surgical treatment for right AAOCA associated with ischemic symptoms or myocardial ischemia. Our aim in this review is to expose the rationale for percutaneous coronary intervention in right AAOCA with interarterial course and to present the published results.